IL-33-Mediated Protection against Experimental Cerebral Malaria Is Linked to Induction of Type 2 Innate Lymphoid Cells, M2 Macrophages and Regulatory T Cells - Besnard, Anne-Gaelle (PLoS Pathog, 2015)
Cerebral malaria (CM) is a complex parasitic disease caused by Plasmodium sp. Failure to establish an appropriate balance between pro- and anti-inflammatory immune responses is believed to contribute to the development of cerebral pathology. Using the blood-stage PbA (Plasmodium berghei ANKA) model of infection, we show here that administration of the pro-Th2 cytokine, IL-33, prevents the development of experimental cerebral malaria (ECM) in C57BL/6 mice and reduces the production of inflammatory mediators IFN-γ, IL-12 and TNF-α. IL-33 drives the expansion of type-2 innate lymphoid cells (ILC2) that produce Type-2 cytokines (IL-4, IL-5 and IL-13), leading to the polarization of the anti-inflammatory M2 macrophages, which in turn expand Foxp3 regulatory T cells (Tregs). PbA-infected mice adoptively transferred with ILC2 have elevated frequency of M2 and Tregs and are protected from ECM. Importantly, IL-33-treated mice deleted of Tregs (DEREG mice) are no longer able to resist ECM. Our data therefore provide evidence that IL-33 can prevent the development of ECM by orchestrating a protective immune response via ILC2, M2 macrophages and Tregs.